Marijuana Use in Hepatitis C Infection does not Affect Liver Biopsy Histology or Treatment Outcomes - Theresa Liu; Glen T Howell; Lucy Turner; Kimberley Corace; Gary Garber; Curtis Cooper (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Marijuana smoking is prevalent among hepatitis C virus-infected patients. The literature assessing the influence of marijuana on liver disease progression and hepatitis C virus antiviral treatment outcomes is conflicting.